Análise comparativa dos mecanismos de governança das redes agroindustriais avícolas da macrorregião de Ribeirão Preto SP e de Santa Catarina. - Pinotti, Raquel Nakazato (Universidade Federal de São Carlos, 2005)
This text has as objective main to carry through a comparative analysis it enters the power network of being poltry of the macroregion of Ribeirão Preto of the state of São Paulo and of the state of Santa Catarina, taking for base the individual and collective action of the actors and its main dynamic resources of power (constitutional, technological, financial, legal politicians and organizacionais ). From the studies of the characteristics of the actors of each network (number of participants; function, types of relation, structure and distribution of being able), were possible to verify that the catarinense poltry network presents more dynamic resources of power, greater coordination and harmony between its actors. The catarinense network has presence of formal relations of production, significant presence of dynamic resources of power and the legitimacy of the great industrial firms in the coordination of the system of integration and the network, while that the São Paulo network presents sufficiently distinct configuration: more types of actors (the independent agricultural producers, the intermediate and the corrector of chicken), low representation of its actors, informal relations of production and minor presence of dynamic resources power. In this context, it was possible to conclude that the networks possess trajectories of dependence (path dependence) well distinct, that lead to the structure of the distribution of dynamic resources of power presented.
Keywords: Economia agrícola; Recursos dinâmicos de poder; Avicultura; Governança; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA